Tribological properties of PTFE-based fabric composites at cryogenic temperature - Mingkun Xu; Zidan Wang; Lihe Guo; Liming Tao; Tianbao Ma; Tingmei Wang; Qihua Wang (Friction)
Abstract Fabric composites are widely employed in self-lubricating bearing liners as solid lubrication materials. Although the tribological behaviors of fabric composites have been extensively studied, the cryogenic tribological properties and mechanisms have been scarcely reported and are largely unclear to instruct material design for aerospace and other high-tech applications. Herein, the tribological properties of polytetrafluoroethylene (PTFE)-based hybrid-fabric composites were investigated at cryogenic and ambient temperatures in the form of pin-on-disk friction under heavy loads. The results suggest that the friction coefficients of the hybrid-fabric composites obviously increase with a decrease in wear when the temperature drops from 25 to −150 °C. Moreover, thermoplastic polyetherimide (PEI), as an adhesive for fabric composites, has better cryogenic lubrication performance than thermosetting phenol formaldehyde (PF) resin, which can be attributed to the flexible chemical structure of PEI. The excellent lubrication performance of hybrid-fabric composites is attributed to the transfer film formed by PTFE fibers on the surface of fabrics.